The Theater of Operations : National Security Affect from the Cold War to the War on Terror - Masco, Joseph, 1964- (Book collections on Project MUSE., 2014)
How did the most powerful nation on earth come to embrace terror as the organizing principle of its security policy? In The Theater of Operations, Joseph Masco locates the origins of the present-day U.S. counterterrorism apparatus in the Cold War's 'balance of terror.' He shows how, after the attacks of 9/11, the U.S. global War on Terror mobilized a wide range of affective, conceptual, and institutional resources established during the Cold War to enable a new planetary theater of operations. Tracing how specific aspects of emotional management, existential danger, state secrecy, and threat awareness have evolved as core aspects of the American social contract, Masco draws on archival, media, and ethnographic resources to offer a new portrait of American national security culture. Undemocratic and unrelenting, this counterterror state prioritizes speculative practices over facts, and ignores everyday forms of violence across climate, capital, and health in an unprecedented effort to anticipate and eliminate terror threats--real, imagined, and emergent.